“Supercharged Reality”: Documentary and Theatrical Disciplinarity - Filewod, Alan (Studies in Canadian Literature, 2016)
A review of documentary performance in Canadian theatre over a forty-year span explores how it has continued as a gateway practice that simultaneously enables and refuses theatre disciplinarity, the system of value that differentiates the professional from the amateur, and which produces concepts of excellence and mastery. In the decades since a generation of actor-creators reinvented the theatre profession in Canada by creating texts out of research (following the template of Theatre Passe Muraille’s The Farm Show in 1972), documentary has become institutionalized as a theatrical strategy in which high-affect performance serves as an authenticating convention, giving shows the gloss of disciplinarity that invites credibility in the authority of the text. The sophisticated documentaries of Annabel Soutar suggest that this high-disciplinary mode authorizes work as professionalized culture and exerts influence on the wider theatre community. That documentary continues to function as a means of professional entry and cultural inclusion can be seen in Judith Thompson’s recent work with socially excluded communities, who in their work with the playwright claim theatrical presence by documenting their own experience. Against the highly disciplined work of Soutar and Thompson, the persistence of a low-disciplinary mode that refuses the aesthetic values of professionalized culture shows that reduced theatricality – the representation of a lack of representation – retains tactical power because it can create an image of a rigorous and de-aestheticized fidelity to evidence. Gary Kirkham and Dwight Storring’s verbatim documentary, Rage Against Violence, shows how this low-disciplinary mode is an effective and accessible cultural resource for community activists.